The Feminine Dimension of Digital Nomadism: A Qualitative Analysis of Nomadic Women's Experiences - Sztuk, Aleksandra (Kobiecy wymiar cyfrowego nomadyzmu: jakościowa analiza doświadczeń cyfrowych nomadek, 2025)
Aim: The article aims to present the advantages and disadvantages of the digital nomad lifestyle from a female perspective. The theoretical part also includes the definition of digital nomadism as a global trend and the benefits of acquiring one of the newest target groups of territorial units. The research conclusions focus on territorial marketing, specifically supporting managers in creating appropriate destinations for female mobile workers. Methodology: A qualitative approach was used with a structured interview questionnaire. The research involved 12 women who, at the time of the study, were actively leading a nomadic lifestyle in different parts of the world. Results: The most frequently mentioned advantages of a nomadic lifestyle included freedom and mobility. The women appreciate the sense of autonomy in deciding when and where to work. Regarding the most frequently mentioned disadvantages, the participants mentioned feeling lonely and having difficulties maintaining relationships when frequently changing places of residence. Implications and recommendations: The research allows for a better understanding of challenges and needs facing women related to their mobile lifestyle. The conclusions from the research are addressed to the authorities of territorial units. The implications are related to place marketing and can support the attraction of digital nomads to destinations. Originality/value: The study's value can be attested by the fact that so far only two scientific articles have drawn attention to the female perspective of digital nomadism so far. According to statistics, more women are deciding to fulfill their professional duties in this mode. Given the growing share of women among digital nomads, the research findings shed light on better adapting destinations to their stay.
Ekonomia XXI Wieku = Economics of the 21st Century, 2025, Nr 28, s. 30-39
Keywords: digital nomadism; digital nomads; place marketing; cyfrowy nomadyzm; cyfrowi nomadzi; marketing miejsc